Biocatalytic PVDF composite hollow fiber membranes for CO2 removal in gas-liquid membrane contactor - Xu, Yilin (2020)
A highly efficient biocatalytic carbonic anhydrase (CA)-polydopamine (PDA)/polyethylenimine (PEI)-polyvinylidene fluoride (PVDF) (referred to as CA-m-PVDF) composite membrane was fabricated for CO2 conversion and capture in the gas-liquid membrane contactor (GLMC) process. The co-deposition of PDA/PEI with amino functional groups was employed to amine-functionalize a PVDF substrate as support for subsequent in-situ CA immobilization by cross-linking with glutaraldehyde. This enhances the enzyme stability and prolongs its lifespan, thus facilitates CO2 hydration efficiency in the GLMC process. In this work, different immobilization CA protocols were compared based on the CA activity and activity recovery. For biocatalytic CA-m-PVDF membranes, the best activity of 498 U m−2 (membrane) and a corresponding activity recovery of 31.5% were achieved (m(5 h)-PVDF as support, 0.67 (v/v)% GLU as cross-linking agent, 600 μg mL−1 CA solution, pH 8.0, temperature at 25 °C, and 24 h reaction time). By using water as absorbent with a liquid velocity of 0.25 m s−1 in a bench-scale GLMC setup, a high-efficiency CO2 absorption flux of 2.5 × 10−3 mol m−2 s−1 was obtained, which was ~165% higher than that of the non-biocatalytic m-PVDF membrane. The long-term stability test showed a good enzyme activity for CO2 hydration capacity for the CA-m-PVDF membranes during 40 days of test duration. Overall, the results achieved in this work may provide promising insights into enzyme immobilization on polymeric supports for the development of high-efficiency biocatalytic membranes for CO2 capture in GLMC applications.